The Role Of Fatwa Majelis Ulama Indonesia (MUI) In Asset Forfeiture A Maqashid Shariah Perspective On Legal And Ethical Considerations In Indonesia - Ryan Bianda; Muhammad Yosef Niteh; Maad Ahmad; Suhaila Sharil; Muhammad Fakhrur Razi Shahabudin (Universiti Sains Islam Malaysia, 2026)
The Draft Law on Asset Forfeiture in Indonesia represents a significant legal reform aimed at combating financial crimes such as money laundering and corruption. However, its implementation raises critical ethical and religious concerns, particularly within Indonesia’s Muslim-majority society. This study examines the role of MUI fatwas in guiding asset forfeiture policies, analyzing their alignment with Maqashid Shariah principles—notably hifzh al-mal (protection of wealth) and hifzh al-nafs (protection of life). A descriptive-analytical approach is applied to evaluate legal documents, MUI fatwas, and scholarly discourse on Islamic law and economic justice. The findings reveal that MUI fatwas support asset forfeiture as a tool for justice, provided that procedural fairness and transparency are maintained. The study highlights potential legal and economic risks, including misuse of asset forfeiture laws for political gain and negative impacts on investor confidence. From an Islamic legal perspective, asset confiscation is permissible only under strict judicial oversight, ensuring protection of individual rights while addressing economic injustices. This research contributes to Islamic legal scholarship by bridging the gap between religious interpretations and contemporary financial governance. The findings underscore the necessity of policy refinements to align Islamic ethical standards with modern legal mechanisms. Future research should investigate comparative Sharia-based legal frameworks and assess the long-term socio-economic effects of asset forfeiture in Indonesia.